BISNIS ALA RASULULLAH DALAM PERSPEKTIF PEMASARAN - Yusron Ali Sya'bana; M. Yasir Nasution; Sugianto (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
Marketing activities are actually very noble activities because these activities always bring up ideas and creativity to approach, innovate, change and update in many ways. However, when these activities experience disorientation and tend to pursue instant profits, then sometimes these noble and ethical marketing activities turn into stupidity, fraud and rottenness. This phenomenon is what we often see in the world of business and enterprise. We should be able to position the marketing function with ethical and moral values (akhlaqul karimah) so that there are no more deviations that undermine the values and blessings of marketing itself. The concept of prophethood (Nubuwwah) is very relevant as a reference in overcoming current business problems, namely by using a sharia marketing strategy that is carried out by paying attention to consumer needs, good product quality, always available when needed (available) and according to consumer expectations (expectations), promotions are carried out directly and continuously (sustainable), and innovate according to consumer needs.